2022
DOI: 10.1093/annweh/wxab119
|View full text |Cite|
|
Sign up to set email alerts
|

Application of a Fourier Transform Infrared (FTIR) Principal Component Regression (PCR) Chemometric Method for the Quantification of Respirable Crystalline Silica (Quartz), Kaolinite, and Coal in Coal Mine Dusts from Australia, UK, and South Africa

Abstract: This article describes the approach used to assess the performance of a Fourier transform infrared (FTIR) and principal component regression (PCR) chemometric method when measuring respirable quartz, kaolinite, and coal in samples from a variety of mines from different countries; relative to target assigned values determined using X-ray diffraction (XRD). For comparison, FTIR results using the partial least squares regression (PLSR) method are also available. Bulk dusts from 10 Australian mines were scanned us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The authors recommended that, to obtain better FTIR data, spectra should be examined for potential matrix interferences, a peak height ratio method should be used for quantification and filters should not be overloaded. In order to minimise such interferences, a PCR chemometric model was developed 54 using coal dust mixtures on filter samples and verified by comparison with the results from XRD analyses. This model allowed quartz to be measured in several coal dust types with a LOD of 5 μg per filter and met the method performance requirements set out in ISO 20581 if airborne silica concentrations of 100 μg m −3 were to be sampled using a nominal 500 L sample volume.…”
Section: Air Analysismentioning
confidence: 99%
“…The authors recommended that, to obtain better FTIR data, spectra should be examined for potential matrix interferences, a peak height ratio method should be used for quantification and filters should not be overloaded. In order to minimise such interferences, a PCR chemometric model was developed 54 using coal dust mixtures on filter samples and verified by comparison with the results from XRD analyses. This model allowed quartz to be measured in several coal dust types with a LOD of 5 μg per filter and met the method performance requirements set out in ISO 20581 if airborne silica concentrations of 100 μg m −3 were to be sampled using a nominal 500 L sample volume.…”
Section: Air Analysismentioning
confidence: 99%
“…In some reported studies, industrial chemometric analysis is used to understand the movement of pollutants (Grabowski et al, 2021;Vakarelska et al, 2021). Various research has been reported in quantifying the respirable silica emerging from coal mines (Stacey et al, 2022). Still, there needs to be more research on spatial analysis of pollutants emerging from the various activities of the mining operations using chemometric techniques.…”
Section: Introductionmentioning
confidence: 99%